INFESTASI CACING SALURAN PENCERNAAN PADA KAMBING KACANG PERANAKAN ETTAWA DI KELURAHAN AMBAN KECAMATAN MANOKWARI BARAT KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - Purwaningsih, Purwaningsih; Noviyanti, Noviyanti; Sambodo, Priyo (JURNAL ILMIAH PETERNAKAN TERPADU, 2017)
The study was done to determine a general health feature of goat reared on semi intensive system especially on gastrointestinal worms parasites infestation. Research location were chosen based on the higher population in one location home farmers. Thirtytwo goats was 4 weeks – 3 years old that reared in the stage shed model examined fecal sample for knowing prevalence of gastrointestinal worm. The examination method fecal sample used natif and sedimentation methods. Based on the results of investigation fecal sample shows that prevalence of gastrointestinal worm infestation on goat reared in the stage shed model was 100%. The goats were infected with Strongyle sp, Strongyloides sp, Haemonchus spp, Bunostomum spp, Trichostrongilus spp, dan Cooperia spp. Keywords : Infestation,Gastrointestinal Worm, Ettawa Crossbreed Goat, Stage Shed